Limitation factors for the performance of kesterite Cu2ZnSnS4 thin film solar cells studied by defect characterization. Issue 50 (4th June 2015) - Yin, Ling; Cheng, Guanming; Feng, Ye; Li, Zhaohui; Yang, Chunlei; Xiao, Xudong
<x xml:space="preserve">Abstract</x> PL, AS and DLCP have been performed to study the limitation factors for the performance of CZTS solar cells.